2000
DOI: 10.1016/s0896-6273(00)81143-5
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila Trio Plays an Essential Role in Patterning of Axons by Regulating Their Directional Extension

Abstract: We identified the Drosophila trio gene, which encodes a Dbl family protein carrying two Dbl homology (DH) domains, each of which potentially activates Rho family GTPases. Trio was distributed along axons in the central nervous system (CNS) of embryos and was strongly expressed in subsets of brain regions, including the mushroom body (MB). Loss-of-function trio mutations resulted in the misdirection or stall of axons in embryos and also caused malformation of the MB. The MB phenotypes were attributed to alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
192
0
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(207 citation statements)
references
References 36 publications
13
192
0
2
Order By: Relevance
“…It is suggested that Rho is activated via repulsive axon guidance cues, whereas Rac is activated via attractive cues (Mueller, 1999;Awasaki et al, 2000). Inactivation of Rho initiates neurite outgrowth (Jin and Strittmatter, 1997;Lehmann et al, 1999), and perturbations in Rho activity result in directional changes of growing axons (Awasaki et al, 2000).…”
Section: Rho Activity and Direction Of Axonal Outgrowthmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that Rho is activated via repulsive axon guidance cues, whereas Rac is activated via attractive cues (Mueller, 1999;Awasaki et al, 2000). Inactivation of Rho initiates neurite outgrowth (Jin and Strittmatter, 1997;Lehmann et al, 1999), and perturbations in Rho activity result in directional changes of growing axons (Awasaki et al, 2000).…”
Section: Rho Activity and Direction Of Axonal Outgrowthmentioning
confidence: 99%
“…Recently Trio, a unique GEF that has binding domains for both Rac and Rho, has been studied in detail in Dro-sophila (Awasaki et al, 2000;Bateman et al, 2000;Liebl et al, 2000;Newsome et al, 2000). Trio activates Rac selectively by its GEF1 domain, and the GEF2 domain shows specificity for Rho (Debant et al, 1996).…”
Section: Balance Between Rac and Rhomentioning
confidence: 99%
“…Among Dbl-GEFs, several GEFs for Rac have been suggested to participate in nervous system development. Still life (SIF) and Trio in Drosophila, Unc-73 in Caenorhabditis elegans, and Kalirins in mammals were shown to take part in synaptogenesis, neuritogenesis, axonal pathfinding, or dendritic morphogenesis (Sone et al, 1997Steven et al, 1998;Awasaki et al, 2000;Lin and Greenberg, 2000;Penzes et al, 2003). Observations from our group and others also suggested that STEF (SIF and Tiam1-like exchange factor) and Tiam1 (Tcell lymphoma invasion and metastasis 1), both orthologs of Drosophila SIF, are involved in neuritogenesis as well as neuronal migration Kunda et al, 2001;Matsuo et al, 2002;Kawauchi et al, 2003;Matsuo et al, 2003;Tanaka et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Les mutants unc-73 présen-tent de nombreux défauts de migration des cellules neuronales, mais aussi de guidage et de fasciculation des axones [23]. Plusieurs études indépendantes ont identifié l'orthologue de Trio chez la drosophile [24][25][26][27]. Drosophila Trio (D-Trio) a été en particulier isolé par un crible permettant d'identifier des gènes impliqués dans le guidage axonal des cellules photoréceptrices de l'oeil [24].…”
Section: Trio Contrôle L'activation De Plusieurs Gtpasesunclassified
“…Si le rôle du premier domaine GEF de Trio semble être prépondérant dans le contrôle du guidage axonal par D-Trio, celui du second domaine reste obscur. Cependant, dans les mutants trio chez la drosophile, on observe chez l'adulte une extension anormale des dendrites au niveau d'une structure particulière du cerveau, les corps pédonculés, et ce phé-notype est tout à fait similaire à celui observé dans des mutants de la GTPase RhoA [27]. Ainsi, D-Trio activerait Rac via son premier domaine GEF pour contrôler le guidage axonal, et activerait RhoA via son second domaine pour contrôler la morphologie dendritique.…”
Section: Trio Contrôle L'activation De Plusieurs Gtpasesunclassified